Genetically Analysis of Tuberculosis Infected Patients: Understanding the Genetic Basis and Drug Resistance of Tuberculosis (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The incidence of tuberculosis (TB) remains elevated and is a significant public health concern. However, only Mycobacterium tuberculosis, Mycobacterium leprae, Mycobacterium Africanus, Mycobacterium avium are human pathogenic. Though other species can still get poisoned, people are the only host identified for Mycobacterium tuberculosis. When the immune system is impaired, it may contribute to contamination or reactivation of the microorganism if previously contaminated with bacteria. The availability of full laboratory and virulent genome sequencing of the M strain. Tuberculosis has presented researchers with a variety of modern learning and awareness of this microorganism. This article describes the existence at the molecular level of such contagious bacteria, taking into account recent developments in sequencing and drug resistance.